Analisis faktor-faktor yang mempengaruhi tingkat keberdayaan perempuan - Edang Juliana; Tuti Gantini; Nataliningsih; Elly Roos Maria; Yuliana Samantha (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2023)
This study aims to analyze the factors that influence the level of women's empowerment. The method used is survey research with a quantitative verification approach. The research was conducted in Indramayu Regency, using the Multiple Stage Sampling technique. Five (5) sub-districts were taken from 31 sub-districts, and 20 respondents were randomly selected from each sub-district so that the total number was 100 women respondents. Individual characteristics, competence, and availability of information are exogenous variables while the endogenous variable is the level of women's power. Analysis using Structural Equation Modeling (SEM), with calculations assisted by Smart PLS 4 software. The validity test was carried out to see valid indicators based on the loading factor value > 0.5, the reliability test was carried out on the research variables, and the SEM model was obtained in iteration 2. The results showed that individual characteristic variables, competence, and information availability contributed 61% to women's empowerment level. Individual characteristics have a positive effect of 0.77 and are significant on the level of women's empowerment. Women's competence needs to be increased, as well as the availability of information so that women can play an active role and increase their involvement in the economy and development.